Bioaccumulation of 137Cs: Vegetation Responses, Soil Interactions and Ecological Implications in the Northern Taiga Ecosystems - Marina Popova; Nikita R. Kriuchkov; Ivan Myasnikov; Alexei Kizeev; Svetlana Ushamova; Dmitriy Manakhov (Life)
This study presents the first comprehensive examination of 137Cs behavior in northern taiga ecosystems of the Kola Peninsula, a previously understudied region regarding radionuclide mobility. The background radioactive contamination of these ecosystems stems from global fallout and differs from more extensively studied contaminated areas. Twelve monitoring sites at varying distances from the Kola nuclear power plant were established to assess 137Cs accumulation in dominant plant species across three forest tiers. Gamma-spectrometric measurements revealed high mobility of 137Cs with specific activity ranging within 4.7–34.5 Bq/kg in trees, 8.4–164.8 Bq/kg in shrubs, and 15.0–94.5 Bq/kg in mosses. Notably, Ericaceae family plants demonstrated the highest accumulation capacity. 137Cs concentrations were significantly higher at the background site (30 km from the power plant) than in the sanitary protection zone, indicating no detectable influence from the nuclear facility. Strong correlations (up to |rs| = 0.93) between bioaccumulation indicators and soil properties were found—particularly with potassium content, exchangeable cation concentration, and organic matter content—suggesting that soil characteristics primarily determine 137Cs mobility. These findings highlight the potential risk of 137Cs movement through food chains in northern taiga ecosystems, with bioaccumulation coefficients exceeding those of central Russian landscapes and being comparable to those of Scandinavian taiga ecosystems.